Relationship of Illness Perception with Asthma Symptoms Control in Adolescents - Lorensia, Amelia; Lestari, Ayu (Universitas Islam Bandung, 2023)
Asthma has a high prevalence in Indonesia. Good self-management is necessary for therapy and greatly affects the level of asthma control symptoms. The patient's perception plays an important role in the success of asthma therapy, especially among students, because education affects a person's mindset and perception of disease conditions. The purpose was to determine the relationship between illness perception and control of asthma symptoms in adolescents. The method was cross-sectional and was conducted from November 2019 to January 2020. The variables were asthma control and illness perception. This research was conducted on a campus in Surabaya city. Respondents were asked to fill out the Illness Perception Questionnaire (IPQ) and asthma control test (ACT) questionnaire and analyze by calculating each answer point. This study used a chi-square test to analyze the relationship between ACT and Illness perception. This study involved 75 respondents. Of most of the respondents, 58 people have their asthma partially controlled. Most respondents experienced shortness of breath and wheezing symptoms, and most understood that they were related to their asthma. There was a relationship between asthma control scores and illness perception (p>0.05) on the timeline (p=0.03), personal control (p=0.03), and causal representation (p=0.01). Illness perception can affect asthma symptoms. Asthma will be experienced for a long time, and respondents will better adjust their lifestyle and have confidence that it was controlled. Material factors were also considered. If their asthma was controlled, it was hoped not to affect their finances.